Management de Projet en Linguistique Appliquée. : Méthode et Cas d’Usage - Bach, Matthieu (HERMES - Journal of Language and Communication in Business, 2024)
This article examines the application of project management principles in the field of applied linguistics, using the author’s doctoral research experience as a case study. It explores the challenges, strategies, and lessons learned in managing linguistic research projects. By highlighting best practices and encountered obstacles, the study aims to enhance understanding of project management within applied linguistics. The insights provided are valuable for researchers and practitioners navigating the complexities of linguistic research endeavors.